2019
DOI: 10.1136/bmjgh-2018-001220
|View full text |Cite
|
Sign up to set email alerts
|

Teaching patient safety in global health: lessons from the Duke Global Health Patient Safety Fellowship

Abstract: Health systems in low-income and middle-income countries (LMICs) have a high burden of medical errors and complications, and the training of local experts in patient safety is critical to improve the quality of global healthcare. This analysis explores our experience with the Duke Global Health Patient Safety Fellowship, which is designed to train clinicians from LMICs in patient safety, quality improvement and infection control. This intensive fellowship of 3–4 weeks includes (1) didactic training in patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This is surprising, as only 38.0% of participants had actually received patient safety training prior to this study and might be based on poor awareness and little knowledge of this subject rather than actual experience. Patient safety training has been shown to be effective for improvement of patient safety attitudes in various settings, including Palestine [11,13,[30][31][32][33][34][35]. Most of these studies monitored self-reported behaviour and attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising, as only 38.0% of participants had actually received patient safety training prior to this study and might be based on poor awareness and little knowledge of this subject rather than actual experience. Patient safety training has been shown to be effective for improvement of patient safety attitudes in various settings, including Palestine [11,13,[30][31][32][33][34][35]. Most of these studies monitored self-reported behaviour and attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives include "global patient safety challenges" focusing on medications (6), clean care and safe surgical practices; strengthening knowledge transfer and technical capacity; empowering patients and families to serve as safety advocates; a health care professions curriculum guide; developing organizational leadership capacity; technical training for primary care settings; measuring, collecting, and analyzing data on patient safety incidents; and monitoring the efficacy of health care system improvements (2). In the context of challenges faced by developing countries, Johnston et al report on a fellowship to prepare physicians to lead interdisciplinary patient safety initiatives in resource-limited health care environments (7), while Elmonstri et al propose a holistic, integrated, patient-centered approach to improving patient safety that engages political leaders and stakeholders, empowers regulatory bodies, promotes a culture of safety, supports research and technology infrastructures, and prioritizes patient safety in health care education (8).…”
mentioning
confidence: 99%
“…13 Interviews were used to evaluate staff perceptions towards patient safety, as well as barriers and facilitators to programme implementation. Although the SSIs explored all CFIR domains, the interview guide prioritised CFIR constructs based on our prior stakeholder analysis 11 21…”
Section: Methodsmentioning
confidence: 99%